PEMANFAATAN CODING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V MI - Faizah, Kurniyatul (PGMI Department of Institut Agama Islam Ibrahimy Genteng Banyuwangi, Indonesia, 2025)
The purpose of this research is to describe the use of coding in mathematics learning and analyze its impact on improving the understanding of mathematical concepts in third-grade students at MI Tarbiyatus Shibyan. The background of this research is based on the importance of contextual, enjoyable, and relevant learning innovations in the digital era. One potential approach is the integration of coding or simple visual programming, such as Scratch, into the mathematics learning process. The method used was descriptive qualitative, with data collection techniques including observation, interviews, and documentation of teachers and third-grade students. The results showed that the planned use of coding can help students understand mathematical concepts such as number patterns, coordinates, and arithmetic logic through exploratory and creative activities. Students became more enthusiastic and active, and showed improvement in connecting abstract mathematical concepts with digital visualizations. Teachers assessed this approach as relevant and providing a more meaningful learning experience. This research recommends the use of coding as an alternative learning strategy that not only instills an understanding of mathematical concepts but also develops logical, creative, and collaborative thinking skills in third-grade students at MI Tarbiyatus Shibyan Kembiritan Genteng, Banyuwangi.